Strategy Handling of Stunting Based on the Guidebook for Toddler Development in Bondowoso Regency, East Java - Lucy Dyah Hendrawati; Toetik Koesbardiati; Myrtati Dyah Artaria (Biokultur, 2022)
Stunting is a form of growth faltering due to the accumulation of insufficient nutrition that lasts for a long time starting from pregnancy until the age of 24 months. Data from the Bondowoso District Health Office, there are 24.16% or as many as 620 stunting toddlers at the Pujer Health Center in 2020. This number is the highest number of stunting cases in Bondowoso, and the stunting locus village in 2021 is in Alassumur Village, Pujer District. The purpose of this community service is to find out what factors are related to the incidence of stunting and to make a guidebook for toddler growth and development which is intended for health workers, posyandu cadres, and mothers of toddlers. The method used in this community service program is by measuring and interviewing. Measurements were made using anthropometric measurements including height or body length, weight, head circumference, arm circumference, triceps fat thickness, and subscapular fat thickness. Subjects were 128 children, the results showed that 22% or 28 children had stunting or short nutritional status and 13% or 16 children had very short nutritional status. The results of community service that have been carried out show that there are still stunting cases, the main cause being the high cases of early marriage and poor sanitation.